Due Process of Law and the USCCB Essential Norms - Austin, Brian T. ca. 20./21. Jh. (Studia canonica, 2017)
On 15 May 2006, the second revised edition of the USCCB’s decree Essential Norms for Diocesan/Eparchial Policies Dealing with Allegations of Sexual Abuse of Minors by Priests or Deacons came into effect. More than ten years later, certain questions remain. Section one of this article considers the legality of the Norms, in particular the question of the apparent absence of a special mandate. Section two considers prescription in cases of clerical sexual abuse of minors, in particular the question of the interpretation of the faculty granted to the CDF to derogate from the terms of prescription on a case by case basis. Section three considers the right of defense, in particular the right of the accused to some form of contradictorium.